PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X SMA NEGERI 1 PANCUNG SOAL - Azura Despia Eliza; Mohammad Hafrison (EDU RESEARCH, 2024)
The aim of this research is to examine the effect of using a group investigation type cooperative learning paradigm on the ability of class X students at SMA Negeri 1 Pancung Soal in writing negotiation texts. This research focuses on the challenges students face in writing, including difficulties developing ideas and a lack of understanding of the structure of negotiated texts. The research method used was an experiment with a One Group pretest-posttest design. The research results show that the application of the Group Investigation type cooperative learning model can significantly improve students' negotiation text writing skills. Students involved in small groups actively collaborate to complete assignments, gather information, and discuss the results of their work. Through these interactions, students not only learn from teachers, but also from peers, which encourages their motivation and interest in learning. This research concludes that the cooperative learning model which emphasizes active student participation is effective in improving writing skills, especially in the context of negotiated texts. Therefore, it is recommended that teachers apply this model in the learning process to achieve better results in students' writing skills. It is hoped that this research can contribute to the development of innovative learning methods in schools.